2007
DOI: 10.1071/sb06044
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of the Rubus fruticosus aggregate (Rosaceae) and other exotic Rubus taxa in Australia

Abstract: Exotic Rubus taxa in Australia have been revised following consultation with European and North American experts in Rubus, allied with studies of variation in patterns of DNA restriction fragments and morphology. Many of these taxa have names that are applied for the first time in Australia (prefaced with a †). The major focus of the work was the Rubus fruticosus L. aggregate and taxa of this aggregate covered here are R. anglocandicans A. Newton, R. cissburiensis W.C. Barton & Ridd., †R. echinatus Lindl.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 33 publications
(54 reference statements)
0
29
0
1
Order By: Relevance
“…The introduction of Himalayan blackberry to North America was part of a larger initiative in the 19th century to intentionally introduce clones of the R. fruticosus aggregate outside of their native range for fruit production (Hall 1990). Areas of introduction included North and South America, Australia, New Zealand, and South Africa (Evans et al 2007; USDA-ARS National Genetic Resources Program 2011). It was introduced to the Pacific Northwest region for cultivation in 1885 (Jennings 1988;Soll 2001;Murphy 2006) by Luther Burbank (Ceska 1999;Murphy 2006), a botanist, as Himalayan Giant (Hummer 1996).…”
Section: Historymentioning
confidence: 99%
“…The introduction of Himalayan blackberry to North America was part of a larger initiative in the 19th century to intentionally introduce clones of the R. fruticosus aggregate outside of their native range for fruit production (Hall 1990). Areas of introduction included North and South America, Australia, New Zealand, and South Africa (Evans et al 2007; USDA-ARS National Genetic Resources Program 2011). It was introduced to the Pacific Northwest region for cultivation in 1885 (Jennings 1988;Soll 2001;Murphy 2006) by Luther Burbank (Ceska 1999;Murphy 2006), a botanist, as Himalayan Giant (Hummer 1996).…”
Section: Historymentioning
confidence: 99%
“…Pathogenicity of isolates from the trap garden in France was classified as high (H) when>60% of inoculated (detached) leaflets or at least one of the inoculated leaves on whole shoots in each of the replicates were given a disease score of 3 or 4 (Table 4). Pathogenicity was classified as low (L) for all other isolateclone combinations, or non-pathogenic (N) if no uredinia whatsoever were produced on any of the leaflets inoculated in either bioassays (disease score of 0 or 1; Evans et al (2005) c Based on DNA phenotypes published in Evans et al (2007) d Detached-leaflet bioassays were performed in Montpellier (for isolates 6-4, 21-1, 28-2 and 32-2) or Canberra (for remaining isolates), while all whole-shoot bioassays were performed in Canberra only. Bold letters correspond to final ratings obtained in whole-shoot bioassays, except those for isolates on clones KE1 and EB22, which are based on results from both the detached-leaflet and whole-shoot bioassays unless indicated otherwise.…”
Section: Pathogenicity Bioassaysmentioning
confidence: 99%
“…We now know that blackberry in Australia comprises at least 15 polyploid agamospecies, each with one or more genotypes, and one diploid, sexual species (Evans et al 1998(Evans et al , 2007, with Rubus anglocandicans the most widespread of these agamospecies (Evans and Weber 2003). Evans et al (2011) identified at least one Australian isolate capable of infecting the range of blackberry genotypes that have been characterised so far.…”
Section: Introductionmentioning
confidence: 98%
“…The distributions of various taxa of the R. fruticosus agg. can be found in a recent taxonomic update on exotic Rubus in Australia (17). Blackberry infestations in Australia may be discontinuous or continuous and of various sizes and shapes.…”
mentioning
confidence: 99%
“…There are at least 15 taxa of European blackberry (Rubus fruticosus L. aggregate) in Australia, where this plant is regarded as an invasive species, infesting nearly 9 million hectares of land (17,41). Taxa of the R. fruticosus agg.…”
mentioning
confidence: 99%